Exploring the U.S. Coast Guard's stance agility on Twitter during Hurricane Harvey. (4th August 2020) - Boman, Courtney D.; Valiavska, Anna; Bramlett, Josh C.; Cameron, Glen T.
Abstract: Drawing on the contingency theory of strategic conflict management, this study examines how the U.S. Coast Guard (USCG) used Twitter to communicate during Hurricane Harvey. A content analysis was conducted on tweets ( N = 273) by using stances along the contingency's continuum, finding that the USCG frequently adopted stances on both sides of the continuum's spectrum throughout the disaster event. The analysis of USCG tweets provides a real‐world case study of how Twitter is used by organizations to strategically communicate with the public during a disaster event. Like many disaster aid organizations, the USCG must balance competing goals of assisting the impacted population, while continuing to secure funding from the U.S. government. The current study contributes to contingency theory of strategic conflict management literature by applying the theory to a disaster, providing tangible evidence that disaster communication research should consider incorporating different stances across the continuum, sometimes simultaneously, that could help guide strategies, ultimately helping the organization and public being affected during a disaster.